The role of neutrophil extracellular traps in necrotizing enterocolitis - Klinke Petrowsky, Michaela; Chaaban, Hala; Boettcher, Michael (Frontiers in Pediatrics, 2023)
Necrotizing enterocolitis (NEC) continues to be one of the most common causes of mortality and morbidity in preterm infants. Although not fully elucidated, studies suggest that prematurity, formula feeding, imbalanced vascular supply, and altered bacterial colonization play major roles in the pathogenesis of NEC. NEC is characterized by increased cytokine release and leukocyte infiltration. Recent data from preterm infants and animal models of NEC suggest that neutrophil extracellular traps (NETs) are released in intestinal tissue. The contribution of NETs in the pathogenesis and/or prevention/treatment of this disease continues to be controversial. Here, we review the available data on NETs release in NEC in human patients and in different NEC models, highlighting their potential contribution to pathology and resolution of inflammation. Here, we review the available data on NETs release in NEC in human patients and the different NEC models, highlighting their potential contribution to pathology or resolution of inflammation.